Bioluminescence Resonance Energy Transfer (BRET)‐coupled Annexin V‐functionalized Quantum Dots for Near‐Infrared Optical Detection of Apoptotic Cells. (18th October 2017) - Tsuboi, Setsuko; Jin, Takashi
Abstract: Deregulation in apoptosis induces numerous diseases such as cancer, cardiovascular, and neurodegenerative diseases. Detection of apoptotic cells is crucial for understanding the mechanism of these diseases and for therapy development. Although optical imaging using visible‐emitting fluorescent probes, such as FITC‐labeled annexin V, is widely used for the detection of apoptotic cells, there are very limited probes that can be used in the near‐infrared region (NIR) over 700 nm. Compared with visible light, NIR light is highly permeable in turbid biological samples and tissues. In addition, optical imaging in the NIR region shows low autofluorescence from biological samples, leading to clearer images with high signal to background ratios. Here, we report the synthesis of bioluminescence resonance energy transfer (BRET)‐coupled annexin V‐functionalized quantum dots (QDs) and their application to NIR optical detection of apoptotic cells. Abstract : BRETter detection : Deregulation in apoptosis induces numerous diseases such as cancer, cardiovascular, and neurodegenerative diseases. Detection of apoptotic cells is crucial for understanding the mechanism of those diseases and for therapeutic development. We report near‐infrared optical detection of apoptotic cells using BRET‐coupled annexin V‐functionalized CdSeTe/CdS quantum dots.